THE REMOTE SENSING IMAGERY, NEW CHALLENGES FOR GEOLOGICAL AND MINING MAPPING IN THE WEST AFRICAN CRATON - THE EXAMPLE OF CÔTE D'IVOIRE - (:unkn) unknown (My University, 2013)
This paper is a synthesis of the evolution on the use of remote sensing imagery for geological and mining mapping in West Africa, particularly in Côte d'Ivoire. For nearly 50 years, the development of countries in West Africa is mainly based on agriculture. Given the very low prices of export commodities on the world market, governments have adopted other economic policies including, in particular, the exploitation of natural mineral resources. This is as well as several countries saw their economy go on thanks to these natural resources. This is the case of Ghana (gold); Sierra Leone (gold and diamond); and Nigeria (for petroleum). For a decade, mining research has experienced rapid development in some countries in West Africa (Ghana, Mali, Guinea, Côte d'Ivoire, Burkina Faso, Sierra Leone...). This mining research, which is based in part on geological mapping, seems to depend on good geological maps of the affected areas of the West African Craton. It is therefore important to have access to recent and precise maps. It is consequently necessary to use new technologies to resolve the one of the major problems to which ones are confronted the geologists: the lack of sufficient outcrops in the humid tropics of West Africa to achieve accurate maps. Therefore, remote sensing imagery appears to be one of the effective tools for achieving accurate geological maps, essential supports for searching mineral resources. It is necessary that a particular methodology must be known by geologists for a better use of remote sensing imagery.
Keywords: African Research